Diving behavior of Cuvier's beaked whales off Cape Hatteras, North Carolina - Shearer, Jeanne; Quick, Nicola; Cioffi, William; Baird, Robin; Webster, Daniel; Foley, Heather; Swaim, Zachary; Waples, Danielle; Bell, Joel; Read, Andrew (Dryad Digital Repository, 2019)
Behavior data from satellite-relayed Wildlife Computers Mk10 Splash tags deployed on Cuvier's beaked whales off Cape Hatteras, NC.